The preventive effect of Mangifera foetida L. leaf extract administered simultaneously to excess iron on markers of iron overload in Spraque-Dawley rats (Faculty of Medicine Universitas Indonesia, 2017)
Background: Recently, there is no agent available for the prevention of iron overload (IO) in thalassemia patients. Previous studies showed that Mangifera foetida L. leaf extracts reduced the levels of iron in IO in vitro and in vivo models. The present study aimed to determine the efficacy of Mangifera foetida L. leaf extract in the prevention of IO induced in rats.Methods: Thirty male Sprague-Dawley rats were divided into 5 groups: control (untreated), IO, 3 treatment groups with leaf extract equivalent to 50, 100, and 200 mg of mangiferin per kg BW. Fe-dextran (15 mg) was administered intraperitoneally twice a week for 4 weeks to all groups except control (IO, DSM50, DSM100, and DSM200). Urine and blood samples were taken before and after treatments. After 4 weeks of treatment, rats were terminated, and samples of spleen, liver, and heart were taken. Ferritin and mangiferin levels and SOD activities were determined in plasma. Iron levels were measured in plasma, urine, and spleen.Results: Experimental IO increased plasma Fe content 4.23 times and plasma ferritin levels 6.9 times vs normal. Mangifera foetida L. leaf extract DSM50 resulted in the highest blood levels of 212 ng mangiferin per mL and moderately, although not significant, prevented increased plasma ferritin levels and IO in organs and protected against oxidative stress.Conclusion: Aqueous Mangifera foetida L. leaf extract may be useful to prevent IO and oxidative stress in thalassemia patients.